NEW CHALLENGES IN ABRASIVE WATER JET MACHINING - CATALINA CIOFU; CATALIN TAMPU; EUGEN HERGHELEGIU; COSMIN ALEXANDRU IANCU; GHEORGHE BRABIE (Journal of Engineering Studies and Research, 2019)
Abrasive water jet machining (AWJM) is one of the most important method used in cutting different types of materials: alloy sheet, marble, glass, rocks. This process is used in the aeronautic, automotive, metallurgy industries and even in some art techniques and textile industry. The method consists in transforming the kinetic energy of a solid particle directed with water jet at a high pressure to remove material through erosion and abrasion. AWJM is low cost equipment compared to other conventional cutting technologies. This paper is an attempt to review the achievements made in AWJM technology for different hardness materials.